Effect of cryogenic grinding on phenolic compounds and antioxidant properties of fenugreek (Trigonella foenum-graecum L.) seed extract - Sharma, R Saxena, P Barnwal, S N Saxena, P Saxena, S S Rathore, L K (Journal of Spices and Aromatic Crops, 2016)
Effect of cryogenic grinding on oil content, total phenolics, flavonoid content and anti-oxidant properties of seed extract of three fenugreek (Trigonella foenum-graecum) genotypes AM 1, RMt 1 and RMt 305 have been analyzed. Oil content was 37.36% more in cryogenically ground sample of genotype AM 1. Yield of methanol crude seed extract was 76.75% more in cryo ground sample of genotype AM 1. Total phenolic content (TPC) was also high in cryo ground samples of all three genotypes. It ranged from a minimum of 75.72 mg in RMt 1 to a maximum of 94.03 mg gallic acid equivalent (GAE) g-1 crude seed extract in genotype AM 1. Similarly total flavanoid content (TFC) was also increased in all cryogenically ground samples and ranged from 17.75 mg in RMt 305 to 26.37mg quercetin equivalents g-1 crude seed extract in genotype AM 1. Methanol crude seed extract of all genotypes were evaluated for its antioxidant activity in terms of total antioxidant content (AOC), 1, 1-Diphenyl-2-picrylhydrazin (DPPH) free radical scavenging % and EC50 value. The amount of total antioxidant content in cryo ground seeds was significantly high in all genotypes ranging from 9.32 mg in genotype RMt 1 to 11.08 mg butyl hydroxyl toluene (BHT) Equivalent g-1 crude seed extract in RMt 305. DPPH scavenging % was invariably more in cryo ground seeds in all three genotypes. Higher concentration of antioxidant content and DPPH scavenging % suggested high antioxidant activity in cryo ground samples.